Choral performance interaction: Relating movement variation and tuning variability - Ordás, Manuel Alejandro (2017)
GAPS is about the arts and the people who create and appreciate them, from a psychological perspective. The arts include auditory arts (music, sound design), visual arts (painting, architecture), literature, drama, opera, digital arts, and so on. We will focus on music. There will be about 8 research presentations at each hub. There will also be 3 keynotes, which will be viewed by all hubs. GAPS will be the world’s first semi-virtual academic conference. GAPS will strike a new balance between face-to-face and virtual communication, and between activities on different continents, to create a truly global conference. Every talk will be both live and virtual — presented to a live local audience and viewed elsewhere, either in real time or with a time delay. Live and virtual presentations will run in parallel at every hub.